Impact of Storage Temperature Regimens and Protective Media Composition on Rabies Virus CVS Strain Preservation - Varianytsia , Viktoriia; Vysekantsev, Igor (Problems of Cryobiology and Cryomedicine, 2020)
The impact of protective media supplemented with sucrose, glycerol, and maltose on the rabies virus CVS strain preservation during storage at 37, 5, –20, –80, and –196ºC has been studied. The temperature regimen of 37ºC was found as not suitable for virus storage, but temperature of 5ºC could be used for a short-term storage in corresponding protective medium in case of production need. It was shown that storage at –80 and –196ºC in DMEM-based preservation media containing 0.5% fetal bovine serum, supplemented with either 5% sucrose, or 5% glycerol, or 5% maltose, or sucrose and glycerol mixture provided high levels of the rabies virus CVS strain infectious activity within 24 months (observation period). At –20ºC, in a growth medium with sucrose and mixture of sucrose and glycerol, after 6 months 79–82% of the initial virus activity were preserved, and after 12 months that was 69–72%. Upon reaching –80ºC and during subsequent storage of virus samples at this temperature in the studied preservation media, the secondary crystallization of concentrated dissolved substances was prolonged. Probl Cryobiol Cryomed 2020; 30(2): 148–157